A population-based analysis of suicidality and its correlates: findings from the National Mental Health Survey of India, 2015–16. (January 2020) - Amudhan, Senthil; Gururaj, Gopalkrishna; Varghese, Mathew; Benegal, Vivek; Rao, Girish Nagaraja; Sheehan, David Vincent; Kokane, Arun Mahadeo; Chavan, Bir Singh; Dalal, Pronob Kumar; Ram, Daya; Pathak, Kangkan; Lenin Singh, Raj Kumar; et al.
Summary: Background: India accounts for 18% of the global population and 26·6% of global suicide deaths. However, robust population-based, nationally representative data on suicidality are not readily available to plan and implement suicide prevention programmes in India. We aimed to investigate the prevalence and sociodemographic differentials of suicidality using data from the National Mental Health Survey (NMHS) of India, 2015–16. Methods: Trained field data collectors from the NMHS obtained information on suicidality (during the past month) from a community sample of adults aged 18 years and older using the suicidality module of the Mini-International Neuropsychiatric Interview (version 6.0). Suicidality was categorised as low, moderate, high, and overall (representing any suicidality), and examined for sociodemographic differentials using normalised sampling weights. For each of the 12 surveyed states, we calculated the age-standardised suicidality prevalence for men and women, men-to-women ratio of weighted suicidality prevalence, ratio of suicidality to suicide deaths, and ratio of suicide attempts to suicide deaths. We used logistic regression analysis to examine the association between sociodemographic factors and overall suicidality and severity. Findings: Among 34 748 participants with complete interviews, 5·1% (95% CI 4·7–5·6) had some level of suicidality, and 0·3% (0·2–0·4) had at least one suicide attempt in the past month. The prevalence of overall suicidality was higher in women (6·0% [5·4–6·6]) than in men (4·1% [3·7–4·6]). The prevalence of overall suicidality was highest in those aged 40–49 years among women and in those aged 60 years or older among men. Compared with their counterparts, individuals with lower educational attainment, individuals residing in urban metropolitan cities, individuals who were widowed, separated, or divorced, and unemployed individuals had a higher prevalence of overall suicidality. The men-to-women ratio of overall suicidality prevalence for India was 0·68 (range 0·55–0·85). For every death by suicide in India, there were more than 200 people with suicidality and more than 15 suicide attempts. We found variations for various severities of suicidality. We found an increased risk for overall suicidality in women versus men (odds ratio [OR] 1·54 [95% CI 1·31–1·81]; p<0·0001) and in individuals residing in urban metropolitan cities versus those residing in rural areas (1·75 [1·30–2·35]; p=0·0002). Individuals belonging to the lowest income quintile (reference group with OR <1·00 and p<0·05 for other income quintiles), those with depressive disorders (28·78 [20·04–41·33]; p<0.0001) and those with alcohol use disorders (6·52 [3·83–11·10]; p<0.0001) had an increased risk for high suicidality, compared with their corresponding counterparts. Interpretation: A national suicide prevention strategy that is comprehensive, using multisectoral approaches, is required to address the prevailing sociodemographic and other risk factors for reducing suicidality and suicide deaths in India. This study also has implications for other low-income and middle-income countries in south Asia, where sociodemographic factors play a crucial role for suicide prevention. Funding: Ministry of Health and Family Welfare, Government of India.